Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences, 2022)
This edition of KIU Journal of Social Sciences focuses on Development Administration and Educational Psychology. The first part of the Journal addresses issues in Development Administration such as Fiscal Policy, Economic Repositioning, Social Corporate Resposibility, Rural Development, International Business, Tourism and so on. It is argued in one of the papers that corporate organizations that engage in philanthropic activities such as corporate social responsibility enjoy a sense of satisfaction and/or fulfillment by benefiting other people and developing the host community. As the solutions to the challenges Social Corporate Resposibility, the paper recommends among others that corporate entities should adopt the practice of corporate social responsibility by developing their host communities, employing people, creating jobs and advancing skill development. Papers in the second section are on Educational Psychology. Using some private universities in Ogun State, Nigeria as case studies, one of the papers in these sections argues theoretically and demonstrates empirically that self-awareness related significantly to task performance of the academic staff of private universities. It is therefore recommended that the management of private universities should train their academic staff to acquire the competencies associated with self-awareness because a thorough understanding of oneself is an important determinant self-efficacy for improving personal performance. In all, this issue of KIU Journal of Social Sciences features many interesting research papers. Some of these papers are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them. Readers are therefore advised to make proper use of the ideas presented by the various authors.